A review on the applications of rukhsoh in medical practices - Che Mohamad, Che Anuar; Roslan, Rosazra; Sharifudin, Mohd Ariff; Taib, Mai Nurul Ashikin (2015)
Rukhsoh (permit) is a concessionary law, which oppose to azimah (enforced) in Islamic jurisprudence. It is considered as one of the important concept to be understood by Muslims physicians and scientists as its applications offer solutions for hardships and difficulties in performing practical acts of worship. However, discussions regarding this matter in both classical references and current literatures of Islamic Jurisprudence are generally limited and less structure. This review attempts to deliver a structured account on the principles and applications of rukhsoh in medical issues related to practical acts of worship. This review comprises of two parts of discussion. The first part starts with an overview on the general discussion of rukhsoh i.e. concept of rukhsoh in Islamic jurisprudence, evidences from the Quran and Sunnah, as well as relevent qawaid fiqhiyyah. It then follows with the discussion on types of rukhsoh and their determining factors. The general principles in applying the concept of rukhsoh in ibaadah will also be outlined and discussed. The second part of this review attempts to outline the criteria to be fulfilled in order to introduce the concept of rukhsoh into various fiqh issues related to medical practices. The review then delves into specific discussions, which focus into real practical issues which necessitates the application of rukhsoh in different medical disciplines: obstetric and gynaecology, surgery, orthopaedics, and others. The discussions will revolve around the specific medical diseases or conditions, which jeopardize patients’ ability to conduct their act of worship and how the rukhsoh would come into place.